Decision-Making Process of the United States Withdrawal from Afghanistan in 2020-2021 - Diphda, Bintang Corvi; Safira, Putri Alyaa; Ramadhani, Yoga; Gultom, Gertha Maria; Foraihmbarasi, Angelique Kishiola Prima (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
This article explains why the United States chose to withdraw troops from Afghanistan in 2020-2021 by applying Graham Allisons decision-making models. Using a qualitative desk review, this article systematically identified, selected, and analysed secondary sources, then conducted a thematic analysis aligned with the Rational Actor, Organisational Process, and Bureaucratic Politics frameworks. The findings show that, as a rational actor, the U.S. pursued strategic aims of cost reduction, force protection, and fulfilment of political commitments, enabled in part by the Doha framework. Organisational procedures within the Department of Defence, the State Department, and CENTCOM shaped the pace, sequencing, and modalities of withdrawal. Bureaucratic bargaining among the President, senior defence leaders, and the special envoy structured key choices and trade-offs. This article concludes that the exit was driven by rational goals filtered through institutional routines and interagency politics. Policy implications include earlier whole-of-government planning, tighter diplomatic coordination with partners, and robust contingency arrangements.